Do changes in the minimun wage affect younger and older workers differently? Evidence for Paraguay using semi-parametric methods - Angel-Urdinola, Diego; Wodon, Quentin (Estudios de Economía, 2016)
Semiparametric methods have been used to asses the impact of policies such as changes in the minimum wage on the distribution of wage earnings. While the methods are in the spirit of the Blinder-Oaxaca decomposition, they help to differentiate impacts according to where individuals are located in the distribution of wages, and thereby to measure impacts on wage inequality apart from average wages. In this paper, using recent repeated cross-section data from Paraguay for 1993 and 2001,we show how to use semiparametric methods to assess on different groups, such as younger and older workers. We find that changes in the minimum wage have much larger mean and distribution a effects on younger than older workers.